PENGARUH LINGKUNGAN KERJA DAN KOMPENSASI TERHADAP KEPUASAN KERJA KARYAWAN PADA KANTOR PUSAT PDAM KOTA SEMARANG - Desi Kurnia Putr1; Nawazirul Lubis; Wahyu Hidayat (Universitas Diponegoro, 2013)
PDAM is a company who have to proceed drinking water or clean water in order to maintain public welfare. Work environment and compensation is supporting factors to reached an optimal job satisfaction. A company’s goal will be achieved as well as job satisfaction get higher.The purpose of this research is to determine the influence of work environment and compensation on employees job satisfaction at central Office PDAM Semarang. The type of this research is Explanatory Research with data collection techniques by interviewing using questionnaire. Analysis of data using simple linear regression and multiple regression test with SPSS 16.0. While hypothesis testing using the t test, f test, correlation coefficient, and the coefficient of determination. The results showed that working environment has an influence on job satisfaction with a correlation coefficient of 0.464 and a coefficient of determination of 21.5%, the compensation has an effect on job satisfaction with a correlation coefficient of 0.522 and a coefficient of determination of 27.2%, the working environment and compensation together have influence on job satisfaction with the equation Y = 4.150 + 0.107 X1 + 0.237 X2. This means a good working environment and compensation, it will get higher work satisfaction.The conclusion of this research is work environment and compensation has an influence on job satisfaction. Suggestion for the company, needs to improve the working environment in order to give a comfortable workplace and the company needs to review the compensation policy for its employees so that employees feel satisfied, and in the end they will be more motivated to improve their performance.work environment.